Agricultural resource access, decision-making and women’s empowerment in climate-vulnerable smallholder agriculture: evidence from Nepal and Bhutan - Begho, Toritseju; Dendup, Sonam; Tshering, Dendup; Nepal, Bigyapti; Joshi, Rajendra (Frontiers in Sustainable Food Systems, 2025)
IntroductionBuilding resilient agri-food systems in the face of climate change challenges requires addressing the gendered barriers that undermine farmers’ adaptive capacity and limit women’s empowerment. This paper examines how inequalities in access to agricultural resources, decision-making authority and information use shape gender-differentiated resilience among farmers in Nepal and Bhutan.MethodDrawing on primary survey data from a random sample of 240 Bhutanese and 300 Nepalese farmers collected in 2022, the study identifies persistent disparities. Women face reduced access to mechanization, pesticides and credit, particularly in Nepal, and exhibit greater risk aversion in adopting new climate-smart and sustainable soil and crop management practices without assured financial benefits. Women are also more likely to adapt rather than strictly follow formal agricultural advice, but are more engaged in climate-smart practices such as composting. These findings highlight how gendered constraints limit women’s ability to respond to climate-related stressors and their recognition as agents of adaptive change. The paper argues for gender-responsive strategies such as equitable access to resources, inclusive extension services and recognition of women’s knowledge and decision-making roles as essential to building climate-resilient food systems. Empowering women in these domains enhances both individual resilience and the collective capacity of agri-food systems to withstand and adapt to climate risks.